Process Parameters and Conditions of Intensified Composting of Kitchen Biowaste - Sluková Melissa; Dzianik František (Journal of Mechanical Engineering, 2023)
Composting is one of the efficient and effective methods of disposal and recovery of biodegradable waste. A favorable and intensified course of the composting process can be achieved by optimal composition of the composted material (moisture, content of organic substances and nutrients, C:N ratio, etc.), and also by optimizing the conditions under which composting takes place (temperature, pH, structure and aeration of the material, etc.). The paper contains a methodology for calculating the composition of composted material and also a methodology for solving the forced aeration process of composted material. More specifically, some process parameters of the intensified composting of a defined amount of kitchen biowaste, taking place in closed composting reactors, are presented and analyzed. Using the material balance of the composting process, the connections between the desired composition of the matured compost, the composition of the composted material and the conditions under which the composting takes place are pointed out. The specified connections enable the composting process to be optimized appropriately.